Analysis of Student Goals in Using E-Learning in Online Learning during the Covid-19 Pandemic in Makassar City - Hilmi, Amalia Zul; Firdausy, Soraya (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to analyze the quality of information that is present in campus E-Learning and the satisfaction of students as E-Learning users in learning in terms of the quality of information during the covid-19 pandemic in the city of Makassar. By distributing questionnaires to 100 research samples, the results obtained simultaneously or simultaneously all indicators of information quality variables, namely intrinsic view (X1), context-based view(X2), and representational view(X3) significantly and positively affect student satisfaction in using E-Learning on online learning during the covid-19 pandemic.